Telehealth Education for Pregnant Women as an Effort to Increase Knowledge about Hypertension in Pregnancy - Ilmiyani, Siti Naili; Faizaturrahmi, Eka; Ernawati; Pathak, Liza (Babali Publisher, 2024)
Background: One of the main indicators of a country's health degree is the Maternal Mortality Rate (MMR). The priority problem for the health sector in Indonesia is the high maternal mortality rate. Knowledge is one of the components of predisposing factors that are important for health behaviors. An Efforts to increase knowledge is by providing health education Method: The research method was quantitative research with a quasi-experiment research (pseudo-experiment). The research design was a one-group pretest and posttest design. The number of respondents who were used as research samples was 56 people. The research was conducted on pregnant women using WhatsApp lectures. Results: From the results of the study, it was found that there was a difference in the average value of knowledge of pregnant women before and after education, where in the pre-test, it was 73.14 with a standard deviation of 27.260 and in the post-test, it was 89.00 with a standard deviation of 14.791. The results of the analysis obtained a p value of 0.001, so it can be concluded that there is a significant difference between the average value of the level of knowledge in the pre-test and post-test. The data analysis used is Paired T-Test. Conclusion: There is a significant difference between the value before and after education through pretest and posttest delivered with telehealth media.